Gap Expansion Between Cranial Bone and Polyether Ether Ketone Implant in Cranioplasty of Pediatric Patients after Decompressive Craniectomy at Follow-up - Chuanwei Wang; Chen Yang; Runlu Zhang; Yuan Zhang; Yanzhao Wang; Liping Ning; Guoran Du; Zhaoxi Sang; Shilei Ni; Xingang Li; Jie Gong (Neurotrauma Reports)
This study aimed to explore the experience and complications of cranioplasty (CP) with polyether ether ketone (PEEK) in pediatric and adolescent patients after decompressive craniectomy (DC). A total of 62 children (aged <18 years) with cranial bone defects due to DC underwent CP with a custom-made PEEK at our department between January 2018 and April 2023. The clinical characteristics, radiological features, surgical conditions, postoperative complications, and follow-up results of these patients were analyzed retrospectively. Kaplan–Meier survival analysis and Cox regression were used to analyze data. The age of the patients ranged from 2 to 17 years. The follow-up periods ranged from 12 to 70 months. Six patients experienced subcutaneous fluid accumulation (9.7%), five experienced epidural fluid accumulation (8.1%), and two experienced scalp inflammation (3.2%), which all were cured before discharge. Seven patients experienced bone gap expansion at the interface between the cranial bone and PEEK during follow-up (11.3%). Univariate analysis showed that DC-CP time interval (<3 months) and age were two influencing factors. Multivariate analysis revealed that age was the most important factor (p < 0.005, hazard ratio = 0.250, 95% confidence interval: 0.096–0.652). No reoperation was performed. Medical follow-ups were carried out further. For pediatric patients with cranial defects after DC who receive CP with a custom-made PEEK, two variables including younger age and too short DC-CP time interval may be unfavorable factors, to make patients experience bone gap expansion at the interface between the cranial bone and the PEEK. Additional data should be collected to validate our conclusions.